2006
DOI: 10.1111/j.1365-3164.2006.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Masked, controlled study to investigate the efficacy of aStaphylococcus intermediusautogenous bacterin for the control of canine idiopathic recurrent superficial pyoderma

Abstract: A masked, controlled study was designed to investigate the clinical efficacy of a staphylococcal autogenous bacterin for the control of canine idiopathic recurrent pyoderma (IRP). Ten dogs with at least three prior episodes of recurrent superficial pyoderma were recruited. All were screened and found to be free of ectoparasitic and fungal disease and failed to respond favourably to a dietary trial. Those exhibiting signs of pruritus responded completely to antibacterial therapy. Haematological and biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
2
18
0
3
Order By: Relevance
“…To the best of our knowledge, there are no evaluated methods for canine superficial pyoderma like the CADESI‐03 for canine atopic dermatitis 14 . We therefore used a modification of a previously reported scoring system 13,15 . All dogs were subjectively evaluated by owners and investigators after two applications (1 week) as follows: excellent (score 3), having complete disappearance of skin lesions after treatment; good (score 2), having apparent improvement with some lesions remaining after treatment; fair (score 1), having no apparent improvement and some newly developed lesions after treatment; or poor (score 0), having exacerbation during treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are no evaluated methods for canine superficial pyoderma like the CADESI‐03 for canine atopic dermatitis 14 . We therefore used a modification of a previously reported scoring system 13,15 . All dogs were subjectively evaluated by owners and investigators after two applications (1 week) as follows: excellent (score 3), having complete disappearance of skin lesions after treatment; good (score 2), having apparent improvement with some lesions remaining after treatment; fair (score 1), having no apparent improvement and some newly developed lesions after treatment; or poor (score 0), having exacerbation during treatment.…”
Section: Methodsmentioning
confidence: 99%
“…14 We therefore used a modification of a previously reported scoring system. 13,15 All dogs were subjectively evaluated by owners and investigators after two applications (1 week) as follows: excellent (score 3), having complete disappearance of skin lesions after treatment; good (score 2), having apparent improvement with some lesions remaining after treatment; fair (score 1), having no apparent improvement and some newly developed lesions after treatment; or poor (score 0), having exacerbation during treatment. The investigators also took digital images and scored skin lesions, including excoriation, erythema, crusted papules and scales, before and after the trial.…”
Section: Randomized Controlled Trial Comparing 2ca and 4cgmentioning
confidence: 99%
“…Accordingly, their use is strongly discouraged. The use of autogenous bacterins 62,63 or commercial bacterial antigens 64 is encouraged. However, very few studies of the efficacy and usefulness of these measures have been reported and further research is necessary.…”
Section: Prevention Of Superficial Bacterial Folliculitismentioning
confidence: 99%
“…Although rare, several episodes of life-threatening infections of humans by S. pseudintermedius have been reported, with the typical route of transmission being through dog bite wounds (17,36). Previously, crude vaccine preparations based on Staphylococcus aureus phage lysate or S. pseudintermedius autogenous bacterin have shown promise as adjunctive therapies for treatment of pyoderma (7,8), and a rationally designed effective vaccine would be a highly desirable means to reducing the suffering associated with the disease.…”
mentioning
confidence: 99%